Cover Picture: Towards a Sustainable Manufacture of Hierarchical Zeolites (ChemSusChem 3/2014). Issue 3 (March 2014) - Verboekend, Danny; Pérez‐Ramírez, Javier
<x xml:space="preserve">Abstract</x> The Cover picture illustrates the importance of considering the ecological and economical footprint associated with the manufacture of newly developed (catalytic) materials. These aspects, which ultimately determine the large‐scale implementation of catalysts, usually receive little attention in the open literature. Prof. Javier Pérez‐Ramírez and Dr. Danny Verboekend consider the case of hierarchical zeolites (HZ), which are superior heterogeneous catalysts for numerous established and emerging applications. Focusing on the use of demetallation treatments, they present approaches to prepare these advanced materials more efficiently by increasing reactor productivity, recycling waste streams, avoiding the combustion of organics, and minimizing work‐up efforts. More detail is given in the Full Paper by Verboekend and Pérez‐Ramírez on page 753, while more information about the research group is available in the Cover Profile (DOI: 10.1002/cssc.201400062).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>